2020
DOI: 10.1097/qai.0000000000002358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HIV and Interpersonal Trauma on Cortical Thickness, Cognition, and Daily Functioning

Abstract: Background: Interpersonal trauma (IPT) is highly prevalent among HIV-positive (HIV+) individuals, but its relationship with brain morphology and function is poorly understood. Setting: This cross-sectional analysis evaluated the associations of IPT with cognitive task performance, daily functioning, magnetic resonance imaging (MRI) brain cortical thickness, and bilateral volumes of 4 selected basal ganglia regions in a US-based cohort of aviremic HIV+ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The average age for fourteen of fifteen studies, (one study reported the age range only) was 40 years. Eight were all-female studies (Malan-Muller et al, 2013 ; Rubin et al, 2017 , 2015 , 2016 ; Spies et al, 2016 , 2012 ; Spies, Fennema-Notestine, Cherner, & Seedat, 2017 ; Womersley, Spies, Seedat, & Hemmings, 2019 ) and two were all-male studies (Deiss et al, 2019 ; Pukay-Martin, Cristiani, Saveanu, & Bornstein, 2003 ), with the remainder (five studies) including both men and women (Clark, Arce Renteria, Hegde, & Morgello, 2018 ; Clark et al, 2012 ; Kapetanovic et al, 2020 ; Lin et al, 2011 ; Watson et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The average age for fourteen of fifteen studies, (one study reported the age range only) was 40 years. Eight were all-female studies (Malan-Muller et al, 2013 ; Rubin et al, 2017 , 2015 , 2016 ; Spies et al, 2016 , 2012 ; Spies, Fennema-Notestine, Cherner, & Seedat, 2017 ; Womersley, Spies, Seedat, & Hemmings, 2019 ) and two were all-male studies (Deiss et al, 2019 ; Pukay-Martin, Cristiani, Saveanu, & Bornstein, 2003 ), with the remainder (five studies) including both men and women (Clark, Arce Renteria, Hegde, & Morgello, 2018 ; Clark et al, 2012 ; Kapetanovic et al, 2020 ; Lin et al, 2011 ; Watson et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…There were ten case-control studies (Clark et al, 2012 ; Kapetanovic et al, 2020 ; Malan-Muller et al, 2013 ; Pukay-Martin et al, 2003 ; Rubin et al, 2017 , 2015 ; Spies et al, 2016 , 2012 , 2017 ; Watson et al, 2019 ) and five cross-sectional studies (Clark et al, 2018 ; Deiss et al, 2019 ; Lin et al, 2011 ; Rubin et al, 2016 ; Womersley et al, 2019 ). Eight studies were longitudinal in design (Malan-Muller et al, 2013 ; Rubin et al, 2017 , 2015 , 2016 ; Spies et al, 2016 , 2012 , 2017 ; Womersley et al, 2019 ) but only one of these presented longitudinal data examining the relationship between childhood trauma and HIV and change in cognition over time (Spies et al, 2017 ) and one examined the relationship between perceived stress and PTSD and NCI over time (Rubin et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations